Physics Teaching Modules in the Merdeka Curriculum Framework Using the Guided Inquiry Model: A Validity Review - Shaliha, Firdayati Amalia; Mastuang, Mastuang; Haryandi, Surya (Jurnal Ilmiah Pendidikan Fisika, 2025)
The lack of valid physics teaching modules in the Merdeka curriculum framework makes it difficult for educators to develop learning tools that meet classroom needs. This research uses the guided inquiry model to measure the validity of physics teaching modules in the Merdeka curriculum framework. This research is categorized as research and development using the ADDIE model. Data was obtained using a validation sheet instrument distributed to two expert validators and one practitioner validator. The data analysis technique used was descriptive quantitative. The results showed that the physics teaching module in the Merdeka curriculum framework using the guided inquiry model was valid and categorized as excellent. This research serves as a reference for developing similar teaching materials, and the module's validity contributes to improving the quality of physics learning in the classroom. The suggestion for future follow-up efforts is to conduct a practicality and effectiveness test.